Penulisan Naskah Pada Pembuatan Video Feature Berdaya, Berkarya, Bermakna bagi Disabilitas - Amanda Putri Julianti; Santi Susanti; Rinda Aunillah Sirait (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Abstract: This writing aims to analyze the scriptwriting process in the production of the feature video Empowered, Creative, and Meaningful for Persons with Disabilities, which highlights the potential of persons with disabilities at the Our Dream Indonesia Foundation in creating creative products and achieving economic independence. It also emphasizes the importance of multisectoral collaboration (government, institutions, society) in building an inclusive ecosystem for persons with disabilities and the need to raise public awareness through visual media to break negative stigmas. This 11-minute feature video is designed with an expository narrative divided into three main components—introduction, development, and conclusion—to present facts informatively while evoking audience empathy. The research findings show that the scriptwriting process is carried out through three main stages: pre-production, production, and post-production. This work also demonstrates that expository narratives are effective in conveying educational messages without sacrificing emotional appeal.